Effect of technological process on antioxidant capacity and total phenolic content of Andean lupine (Lupinus mutabilis Sweet) = Efecto del proceso tecnológico sobre la capacidad antioxidante y compuestos fenólicos totales del lupino (Lupinus mutabilis Sweet) andino - J. S. Cordova-Ramos; P. Glorio-Paulet; A. Hidalgo; F. Camarena (Scientia Agropecuaria, 2020)
The effect of debittering, extrusion and spray drying on antioxidant capacity and total phenolic compounds in non-defatted and defatted flours from three Andean lupine genotypes (Altagracia, Andenes, and Yunguyo) was evaluated. Total phenolic content (TPC; Folin-Ciocalteu method) and antioxidant capacity (DPPH and ABTS+) were assessed by spectrophotometry. Results showed that technological processes decreased significantly (p ≤ 0.05) antioxidants and phenolic compounds. Bitter lupine (control sample) had higher (p ≤ 0.05) TPC and antioxidant capacity than processed samples. In non-defatted and defatted samples, TPC of processed samples varied between 0.64 - 1.10 and 0.75 - 1.33 mg gallic acid equivalent/g d.m. in non-defatted and defatted samples, respectively. The DPPH antioxidant capacity varied between 2.87 - 4.10 and 3.12 - 4.73 μmol Trolox/g d.m., while the ABTS+ antioxidant capacity ranged between 50.65 - 75.56 and 61.63 - 76.88 μmol Trolox/g d.m. in non-defatted and defatted samples, respectively. On the other hand, lipids negatively influenced the quantification of TPC; therefore, the defatted samples had higher TPC. Se evaluó el efecto del desamargado, la extrusión y el secado por aspersión sobre la capacidad antioxidante y los compuestos fenólicos totales en harinas no desgrasadas y desgrasadas de tres genotipos de lupino andino (Altagracia, Andenes y Yunguyo). El contenido de fenólicos totales (TPC; método Folin-Ciocalteu) y la capacidad antioxidante (DPPH y ABTS+) se evaluaron por espectrofotometría. Los resultados mostraron que los procesos tecnológicos disminuyeron significativamente (p ≤ 0,05) antioxidantes y compuestos fenólicos. El lupino amargo (muestra de control) tenía una mayor capacidad de TPC y antioxidante (p ≤ 0,05) que las muestras procesadas. En muestras no desgrasadas y desgrasadas, el TPC de las muestras procesadas varió entre 0,64 - 1,10 y 0,75 - 1,33 mg de ácido gálico equivalente/g b.s., en muestras no desgrasadas y desgrasadas, respectivamente. La capacidad ...